Pengaruh Kepemimpinan, Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan Devisi Quality Control PT. Pahala Bahari Nusantara - Evita Ria Agustina; Sri Wahyuningsih (Journal on Education, 2023)
The purpose of this study was to examine the influence of leadership, motivation, work discipline, and employee performance as the dependent variable. The unit of analysis in this research is the employees of PT Pahala Bahari Nusantara Quality Control division. The total population is 80 people with the determination of the sample using the slovin formula which produces as many as 75 respondents. This study uses the analysis of the Structural Equation Modeling (SEM) model to determine how much independent influence the dependent variable has through the intervening variables, carried out using the lisrel 8.8 program. Data collection techniques in this study using observation techniques, questionnaires, data collection. Data analysis techniques in this study used the Classical Assumption Test, Multiple Regression, Hypothesis Test (t test and F test), and the coefficient of determination. The results of the research show that it is partially known that leadership has a positive and significant influence on the performance of employees of PT Pahala Bahari Nusantara Division of Quality Control. Partially it is known that motivation has a positive and significant influence on employee performance at PT Pahala Bahari Nusantara. Partially work discipline has a positive and significant influence on employee performance. Simultaneously it is known that leadership, motivation, and work discipline have a positive and significant influence on the performance of employees of PT Pahala Bahari Nusantara Division of Quality Control.